A Backward-Looking Analysis of Blending Language Instruction for Healthcare Contexts with Entertainment Media to Improve Mental Health Terminology among Learner Nurses - Kusumawardani, Dr. Rina; Pratama, Arief; Putri, Dr. Dwi Lestari (International Journal of Social Sciences, Language and Linguistics, 2026)
The increasing globalization of healthcare demands that nursing professionals acquire not only clinical expertise but also advanced linguistic competence, particularly in mental health communication. This study presents a retrospective research analysis examining the integration of healthcare-oriented language instruction with entertainment-based media, specifically subtitled audiovisual content, to enhance psychiatric vocabulary acquisition among nursing students. Drawing on interdisciplinary literature from English for Specific Purposes (ESP), second language acquisition, and media-assisted learning, the study investigates how exposure to captioned audiovisual narratives contributes to contextualized vocabulary development, comprehension, and retention.The research adopts a retrospective analytical design, synthesizing findings from prior implementations of audiovisual learning tools and edutainment strategies in educational contexts. It evaluates the effectiveness of integrating subtitled television content, particularly Korean drama series, within structured language instruction frameworks tailored for healthcare learners. The analysis identifies key mechanisms such as multimodal input processing, contextual reinforcement, and emotional engagement as critical drivers of improved lexical acquisition.Findings indicate that combining entertainment media with domain-specific language instruction significantly enhances students’ ability to acquire and apply mental health terminology. The approach facilitates deeper semantic understanding, improves retention, and reduces cognitive barriers associated with abstract psychiatric vocabulary. Furthermore, the integration supports the development of cultural sensitivity and empathy, which are essential for effective mental health care delivery.The study also highlights challenges, including variability in language proficiency, the need for pedagogical scaffolding, and potential over-reliance on entertainment content without structured guidance. Despite these limitations, the research demonstrates that edutainment-based learning models represent a viable and innovative approach for enhancing specialized vocabulary in nursing education.This paper contributes to the growing body of literature on technology-enhanced language learning and ESP by offering a comprehensive framework for integrating audiovisual media into healthcare language instruction. It provides practical implications for curriculum design and suggests directions for future research in multimedia-assisted professional education.